Analisis Pengaruh BI Rate, Kurs, Inflasi, Harga Minyak, dan Harga Emas Dunia terhadap Indeks Harga Saham Gabungan Periode 2016-2019 - Ringga Samsurufika Anggriana; R.A Sista Paramita (Jurnal Ilmu Manajemen, 2020)
This research is to explain the influence of BI Rate, Exchange Rate, Inflation, Crude Oil Price, and World Gold Price toward Composite Stock Price Index (CSPI). Type of research used in causality research with a quantitative approach. The sample was based on monthly time series data from January 2016 until December 2019, using a full sampling method that consists of 48 samples. This research used a multiple linear regression method. The value coefficient of determination (R2) is 0,209, means the independent variables BI Rate, Exchange Rate, Inflation, Crude Oil Price, and World Gold Price explain the dependent variable Composite Stock Price Index (CSPI) up to 20,9% and the remaining 70,1% explained by the other. Simultaneous test result (F test), indicating that BI Rate, Exchange Rate, Inflation, Crude Oil Price, and World Gold Price has a significant effect on the Composite Stock Price Index (CSPI). Partial test result (t-test), indicates that BI Rate, Inflation, Crude Oil Price, and World Gold Price showed an insignificant influence on CSPI, while Exchange Rate harmed CSPI. The practical implication of this research provides information to investors to find out that variables affect toward Jakarta Composite Index (JCI).